IMPLEMENTASI KURIKULUM BERBASIS KARAKTER DALAM PENDIDIKAN ISLAM: STUDI KASUS DI MADRASAH ALIYAH HIDAYATUL MUBTADIIN - Agus Salam (UNISAN JURNAL, 2024)
Implementation of a character-based curriculum has become the main focus in modern education, especially in the context of Islamic education. Madrasah Aliyah Hidayatul Mubtadiin Jati Agung is one of the Islamic educational institutions that applies this approach in an effort to shape students’ character and morals. This research aims to reveal the implementation process, supporting and inhibiting factors, as well as the impact of implementing a character-based curriculum at Madrasah Aliyah Hidayatul Mubtadiin Jati Agung. The research method used is a qualitative descriptive method with a case study approach. Data was obtained through observation, interviews and documentation studies. The research results show that the process of implementing a character-based curriculum at Madrasah Aliyah Hidayatul Mubtadiin Jati Agung involves planning, implementation, evaluation and renewal. Planning involves identifying character values, integration in the syllabus, and development of learning modules. Implementation is carried out through daily learning with the teacher’s active role as facilitator. Evaluations are carried out periodically to evaluate the effectiveness of implementation. Supporting factors in implementing a character-based curriculum include the commitment of school principals and teachers, availability of resources, support from students’ parents, and a conducive school environment. On the other hand, inhibiting factors include a lack of teacher understanding, lack of time and resources, resistance from students, and the demands of the national curriculum which tends to emphasize academic aspects. The impact of implementing a character-based curriculum at Madrasah Aliyah Hidayatul Mubtadiin Jati Agung can be seen in the formation of noble morals, improving the quality of social relations, instilling religious values, developing positive personalities, and increasing student academic achievement. This shows that the implementation of a character-based curriculum is effective in creating an educational environment that is conducive to the formation of good character in the younger generation. This research contributes to further understanding of the implementation of a character-based curriculum in Islamic education and can be a reference for other educational institutions in developing holistic character education.